1995
DOI: 10.2307/1382622
|View full text |Cite
|
Sign up to set email alerts
|

Male Pseudohermaphroditism in the Bowhead Whale, Balaena mysticetus

Abstract: Examination of two bowhead whales, Balaena mysticetus, revealed an unusual assembly of reproductive structures. Although the external phenotype was female, the gonads were underdeveloped testes. In the more thoroughly studied of the two whales, all derivatives of the mesonephric (wolffian) and paramesonephric (mtillerian) ducts were absent, and there was an apparently normal male karyotype (40 autosomes + XY). These findings suggest a failure of androgen expression consistent with the syndrome of complete test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…Considering that maximum OCs values found in the present study (2700 ng g −1 lw) were higher than those found in baleen whales characterized with endocrine disorders (1400 ng g −1 lw) (Tarpley et al, 1995; Hoekstra et al, 2002), the potential for these chemicals to present a health effect in the individuals with the highest concentrations should not be dismissed. Because of the low calf production [females give birth to a single calf every 2 years] (Aguilar, 2001), the grade of isolation (Bérubé et al, 1998, 2002), and the small population size (600 animals) of the Gulf of California fin whales (Urbán‐Ramírez et al, 2005; Díaz‐Guzmán, 2006), even slight impairment of reproduction effectiveness in a small number of individuals could affect the status this population (Bérubé et al, 1998, 2002; Urbán‐Ramírez et al, 2005).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Considering that maximum OCs values found in the present study (2700 ng g −1 lw) were higher than those found in baleen whales characterized with endocrine disorders (1400 ng g −1 lw) (Tarpley et al, 1995; Hoekstra et al, 2002), the potential for these chemicals to present a health effect in the individuals with the highest concentrations should not be dismissed. Because of the low calf production [females give birth to a single calf every 2 years] (Aguilar, 2001), the grade of isolation (Bérubé et al, 1998, 2002), and the small population size (600 animals) of the Gulf of California fin whales (Urbán‐Ramírez et al, 2005; Díaz‐Guzmán, 2006), even slight impairment of reproduction effectiveness in a small number of individuals could affect the status this population (Bérubé et al, 1998, 2002; Urbán‐Ramírez et al, 2005).…”
Section: Discussioncontrasting
confidence: 54%
“…Studies describing hormonal disorders in marine mammals caused by OC exposure have focused principally on odontocetii, and pinnipeds because they accumulate high amounts of OC in their tissues (Fossi et al, 1999; Spinsanti et al, 2006; Hickie et al, 2007). Evidence of contaminant induced endocrine disruption in mysticetii species is relatively limited, however, these chemicals have been associated with transformation of epididymal and testicular tissue in North Pacific minke whales ( B. acutorostrata ) (Fujise et al, 1998; Fossi et al, 2003), pseudohermaphroditism in bowhead whales ( Balaena mysticetus ) from Alaska [440 ng g −1 lw ( n = 71) of ΣDDT] (Tarpley et al, 1995; Hoekstra et al, 2002) and fin whales from the Mediterranean Sea [mean ΣDDT = 5000 ng g −1 lw ( n = 27)] (Fossi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been implicated in affecting sexual or gonadal development, as early as in utero (Yamamoto et al, 1996). Although there is no cause-effect implied, true hemaphroditism has been documented in the St. Lawrence Estuary beluga whale (De Guise et al, 1994) and pseudohermaphroditism in the bowhead whale (Tarpley et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…obs.]. Post-mortem evaluation of 2 bowhead whales (Balaena mysticetus) presumed to be female based on external phenotype revealed the presence of underdeveloped testes but total absence of other reproductive structures derived from either Wolffian or Müllerian ducts [Tarpley et al, 1995]. Chromosome analysis in both individuals revealed a nor- mal male karyotype, 42,XY, and the individuals were considered male pseudohermaphrodites.…”
Section: Sex Reversal and Intersexualitymentioning
confidence: 99%